Nanofiber Composite Reinforced Organohydrogels for Multifunctional and Wearable Electronics - Wen, Jing; Wu, Yongchuan; Gao, Yuxin; Su, Qin; Liu, Yuntao; Wu, Haidi; Zhang, Hechuan; Liu, Zhanqi; Yao, Hang; Huang, Xuewu; Tang, Longcheng; Shi, Yongqian; et al. (Nano-Micro Letters, 2023)
Composite organohydrogels have been widely used in wearable electronics. However, it remains a great challenge to develop mechanically robust and multifunctional composite organohydrogels with good dispersion of nanofillers and strong interfacial interactions. Here, multifunctional nanofiber composite reinforced organohydrogels (NCROs) are prepared. The NCRO with a sandwich-like structure possesses excellent multi-level interfacial bonding. Simultaneously, the synergistic strengthening and toughening mechanism at three different length scales endow the NCRO with outstanding mechanical properties with a tensile strength (up to 7.38 ± 0.24 MPa), fracture strain (up to 941 ± 17%), toughness (up to 31.59 ± 1.53 MJ m−3) and fracture energy (up to 5.41 ± 0.63 kJ m−2). Moreover, the NCRO can be used for high performance electromagnetic interference shielding and strain sensing due to its high conductivity and excellent environmental tolerance such as anti-freezing performance. Remarkably, owing to the organohydrogel stabilized conductive network, the NCRO exhibits superior long-term sensing stability and durability compared to the nanofiber composite itself. This work provides new ideas for the design of high-strength, tough, stretchable, anti-freezing and conductive organohydrogels with potential applications in multifunctional and wearable electronics. Highlights: 1 A nanofiber composite reinforced organohydrogel with multifunctionality is prepared. 2 The composite organohydrogel possesses multiple interfacial bondings and multi-level strengthening and toughening mechanism is proposed. 3 The composite organohydrogel exhibits long-term strain sensing stability and can be used for high performance electromagnetic interference shielding.